Kedudukan Miranda Rules dan Penegakan Hukumnya dalam Sistem Peradilan Pidana di Indonesia - Dwi Seno Wijanarko; Irman Jaya (Jurnal Hukum Sasana, 2021)
Miranda Rules are an important instrument in criminal justice which regulates the rights of suspects during the investigation process (investigation and investigation). These rights are in the form of the right to remain silent during the examination and the right to be accompanied by a legal advisor during the examination and trial process, if he is unable to bring a legal representative, then it is the obligation of the relevant agency to bring him in. This paper seeks to answer two big questions related to the Miranda Rule, namely how is the Miranda Rules concept in realizing a judicial process that still provides protection for the rights of suspects? as well as how Miranda Rules are implemented in a practical level? This paper produces two main languages: First, Miranda Rule is an important point in criminal justice because it concerns the rights possessed by the suspect during the investigation process. As one of the legal states in the world, Indonesia consistently enforces the Miranda Rule marked by the adoption of the Miranda Rule concept into various kinds of laws and regulations relating to the judiciary. Second, although the Miranda Rule plays a big role in law enforcement, in practice there are still many cases of violations against the Miranda Rule. Violation of the enforcement of the Miranda Rule has legal consequences in the form of invalidity of the charges against the suspect, because the charges are based on investigations and illegal statements so that they are null and void. Seeing the urgency of the Miranda Rule in the judicial system, it is necessary to comply with law enforcement, aimed not only at the community, but also at the legal structure as an arrow in law enforcement.